ChemInform Abstract: Helicene‐Based Transition Metal Complexes: Synthesis, Properties and Applications. Issue 45 (23rd October 2014) - Saleh, Nidal; Shen, Chengshuo; Crassous, Jeanne
Abstract Review: 96 refs.